The econometrics of panel data : fundamentals and recent developments in theory and practice - Mátyás, László; Sevestre, Patrick (Advanced studies in theoretical and applied econometrics, 2008)
This volume provides a general overview of the econometrics of panel data, both from a theoretical and from an applied viewpoint. This third edition provides a presentation of theoretical developments as well as surveys about how econometric tools are used to study firms and household's behaviors.